Debtors Responsibilities in Subsidized Home Loan Takeovers Based on Indonesian Ministerial Regulation Number 26/PRT/M/2016 - Toguan, Zulfikri; Ernayani, Rihfenti; Nainunis, Nainunis (Institute of Education and Social Research, 2024)
The transfer of ownership for Subsidized Home Ownership Loans (KPR) is prohibited unless the property has been occupied for over 5 years. Despite this rule, violations frequently occur, highlighting gaps in enforcement and a lack of debtor responsibility in credit repayment. This study addresses two main questions: 1) What are the responsibilities of debtors in taking over subsidized KPR based on Regulation Number 26/PRT/M/2016 at Bela Berlian 3 Housing, Kampar Regency? 2) What are the legal consequences for debtors in such takeovers? Using empirical legal research with primary data, the study found that debtors often fail to meet their obligations, including the misuse of bank funds intended for housing debt repayment. This leads to defaults and breaches of contract. Unauthorized takeovers may result in the withdrawal of KPR subsidies, but enforcement remains inconsistent, causing legal uncertainty for new debtors. The research calls for stronger enforcement to prevent unauthorized KPR ownership transfers.